Biodegradable polyurethane foams based on naturally renewable components - Savelyev, Yu. V.; Markovskaya, L. A.; Akhranovich, E. R.; Savelyeva, O. A.; Parkhomenko, N. I.; Rоbota, L. P. (Reports of the National Academy of Sciences of Ukraine, 2015)
New polymeric materials have been synthesized, by using natural products of the biotechnological origin – exopolysaccharides: xanthane and bacterial cellulose. Their contents are about 2–50 wt%. The basic functional properties of the polyurethane foam (PUF) matrix were not changed with increase of the natural compound content. It is shown that the method of incorporation of exopolysaccharides (EPS) into the reaction mixture, as well as the EPS origin, has a significant effect on the structure and intermolecular interactions in PUFs, allowing one to adjust the functional properties of these polymers.